Development of An Assessment Instrument For The Skill of Making Snow White Cakes For Children With Mild Intellectual Disabilities - Agustina, Anneu; Mastiani, Emay (Universitas Pahlawan Tuanku Tambusai, 2025)
Children with mild intellectual disabilities (ATR) face challenges in developing creativity and vocational skills that are essential for their independence. One of the vocational skills taught is making Putri Salju cookies, given its simple process and ease of replication. Vocational teachers at SLB Aisyiyah Kawalu have difficulty assessing the abilities of children with mild intellectual disabilities in relation to making Putri Salju cookies due to the lack of assessment instruments tailored to this need. The researcher aims to develop an assessment tool needed in the learning process of making Snow White cookies for children with mild intellectual disabilities in grade XI at SLB Aisyiyah Kawalu. This study uses a qualitative descriptive method, with data collected through observation, interviews, focus group discussions, and instrument validation conducted on two vocational teachers at different schools. The assessment instruments were developed based on the following stages: familiarization with tools and ingredients, the process of making Putri Salju cookies, cleaning up tools and ingredients, and maintaining the results. Recommendations were given to teachers to help them develop assessment instruments